The Resilient Society - Furman, Jason (Journal of Economic Literature, 2024)
Jason Furman of Harvard University reviews “The Resilient Society” by Markus K. Brunnermeier. The Econlit abstract of this book begins: “Promotes the view that rather than attempting to avoid risks, societies that are resilient to adverse shocks should be proactively developed, addressing how a resilient social contract can be implemented either by governments or via social norms.”